(untitled) (The International Journal for Scientific Research, 2025)
This study aimed to identify the impact of green sustainability practices—with its dimensions of environmental sustainability, social sustainability, economic sustainability, and green innovation—on civil project management in light of Saudi Vision 2030. The study adopted the descriptive-analytical approach as the most suitable for the nature of the topic. Data were collected through a structured questionnaire distributed to a sample of 236 employees working in civil project management departments across the regions of Riyadh, Makkah, and the Eastern Province. The data were analyzed using the SPSS statistical software. The results of the multiple regression analysis revealed a strong statistically significant effect of green sustainability practices collectively on civil project management, with a correlation coefficient of (R = 0.842) and a coefficient of determination of (R² = 0.709). This indicates that about 70.9% of the variance in the efficiency of civil project management can be explained by the four dimensions of green sustainability practices. The study recommended the integration of sustainability standards throughout all stages of the project life cycle, the implementation of specialized training programs for employees in sustainable management, and the promotion of green technologies and innovations in project management practices.